Nano Si / Ge powder material and preparation method and application thereof
By using initial alloy raw materials containing T-type elements for rapid solidification and acid solution reaction, combined with ball milling or sand milling, nano Si/Ge powder materials with good dispersion were prepared, which solved the problems of high cost and low efficiency of nano silicon powder preparation in the prior art, and achieved efficient and low-cost nano powder material preparation.
Patent Information
- Application Number
- CN202411435851.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-10-16
- Filing Date
- 2024-10-14
- Publication Date
- 2025-04-18
AI Technical Summary
The prior art has problems of high cost, low efficiency and difficulty in mass production when preparing nano-silica powder, especially when mechanical ball milling methods require long time and high cost to obtain fine nano-silica powder.
A nano Si/Ge powder material is prepared by using a method of preparing nano Si/Ge powder material, including selecting initial alloy raw materials containing T elements for rapid solidification, then reacting with an acid solution to separate the diffuse particle phase, and finally obtaining a nano Si/Ge powder material with good dispersion through ball milling or sand milling.
This method can effectively reduce the production cost, improve production efficiency, and can produce large-scale industrial production, solving the problems of high cost and low efficiency of nano-silica powder preparation in the prior art.
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of nano materials, and in particular to a nano Si / Ge powder material and a preparation method and application thereof. Background Art
[0002] Nano silicon powder is a silicon powder with nanometer-scale particle size. It has many unique properties and shows wide application potential in various fields: nano silicon powder is used in the negative electrode material of rechargeable lithium battery, or graphite is coated on the surface of nano silicon powder to be used as the negative electrode material of rechargeable lithium battery, which improves the capacity and charge and discharge cycle number of rechargeable lithium battery; nano silicon powder can be applied to coatings to form silicon nano film, which is applied to the solar energy field; nano silicon powder is mixed with diamond under high pressure to form silicon carbide / diamond composite material, which is used as cutting tool.
[0003] At present, the preparation methods of nano silicon powder mainly include mechanical ball milling synthesis, chemical vapor deposition, plasma evaporation and condensation, etc. 1) Mechanical ball milling / sand milling method: Mechanical ball milling and sand milling method uses the mechanical rolling pressure and shear force generated by mechanical rotation and the interaction between particles to grind larger silicon materials into nano-sized powders. This method requires the addition of grinding aids during the grinding process, which is easy to introduce impurities, the product purity is low, and the particles are irregular in shape. The particle size distribution cannot be effectively controlled, the post-processing is relatively cumbersome, the production efficiency is low, and it is not suitable for large-scale industrial production. 2) Chemical vapor deposition method: Chemical vapor deposition is a technology that uses silane (SiH4) as a reaction raw material to produce nano silicon powder. However, silane as a raw material is a flammable and explosive gas, which is not conducive to transportation and storage. 3) Plasma evaporation and condensation method: The silicon raw material is vaporized into gaseous atoms, molecules or partially ionized into ions through a plasma heat source, and condensed into solid powder through rapid condensation technology. However, this method has extremely high equipment requirements, low output, and extremely high cost.
[0004] Due to the various limitations of the above-mentioned technical level and preparation process, the mainstream method for preparing nano silicon powder in the industry is still mechanical ball milling / sand milling. This method first requires ball milling high-purity silicon ingots for several hours to obtain coarse silicon powder with a particle size of about 5μm, and then sand milling the coarse silicon powder with a particle size of about 5μm with large-particle zirconia beads (particle size 0.5mm-1mm) for several hours to obtain medium-sized silicon powder with a particle size of about 500nm. Finally, the medium-sized silicon powder with a particle size of about 500nm is sand milled for several hours with imported ultrafine zirconia beads (particle size 0.1mm, small particle size, easy to wear and fail) to obtain fine nano silicon powder with a particle size of 120-200nm. Ultrafine nano silicon powder below 120nm requires double the time cost and loss cost to obtain, which is extremely costly and difficult to mass produce. Summary of the invention
[0005] Based on this, it is necessary to provide a method for preparing nano Si / Ge powder to address the above problems.
[0006] A method for preparing a nano Si / Ge powder material, characterized in that it comprises the following steps:
[0007] Step 1: Select an initial alloy raw material containing T elements, melt the initial alloy raw material, and obtain a uniform initial alloy melt containing T elements, wherein the T elements include at least one of Fe, Cu, Mn, Mg, Ca, and Cd; the average composition of the initial alloy melt is A a M b T d , and M includes at least one of Si and Ge, and A includes at least one of Zn, Sn, Pb, Ga, In, Ag, Bi, and Al; wherein a, b, and d represent the atomic percentage content of the corresponding constituent elements, and 70%<a<99.39%, 0.6%<b<29.99%, and 0.01%<d≤9.5%;
[0008] Step 2: The initial alloy melt is prepared into a quick-setting alloy by a rapid solidification technology, wherein the solidified structure of the quick-setting alloy includes a matrix phase and a dispersed particle phase; the melting point of the matrix phase is lower than the melting point of the dispersed particle phase, and the dispersed particle phase is coated in the matrix phase; during the solidification process of the initial alloy melt, the T-type elements in the initial alloy melt are redistributed in the dispersed particle phase and the matrix phase, and are enriched in the matrix phase, thereby depleting the T-type elements in the dispersed particle phase; in the quick-setting alloy, the average composition of the dispersed particle phase is mainly A x1 M y1 T z1 , and the A element therein exists as a solid solution in the dispersed particle phase; the average composition of the matrix phase is mainly A x2 M y2 T z2 , and the M element exists in the matrix phase as a solid solution; wherein 0<x1≤1%, 98.0%≤y1<100%, 0<z1<1.5%; 81%≤x2<99.95%, 0.05%<y2<2.5%, 0<z2<18.95%, z1<d<z2; x1, y1, z1, x2, y2, z2 represent the atomic percentage content of the corresponding constituent elements respectively;
[0009] Step 3, reacting the quick-setting alloy with an acid solution, utilizing the characteristics that the matrix phase in the quick-setting alloy is easy to react and dissolve with the acid solution, while the dispersed particle phase is not easy to react with the acid solution, to achieve the free separation of the dispersed particle phase from the quick-setting alloy, and obtain a solid-liquid mixture consisting of a nano-M powder material mainly composed of the original dispersed particles and the corresponding reaction solution;
[0010] Step 4, separating the solid-liquid mixture obtained above, and repeatedly washing the obtained solid product to obtain an undispersed nano-Si / Ge powder material; the main component of the undispersed nano-Si / Ge powder material is nano-M with passivated particle surface, and the volume percentage of dendritic, branch-like, filamentous, and long rod-like (aspect ratio greater than 3) particles in all nano-M particles exceeds 20%; at the same time, the secondary components of the undispersed nano-Si / Ge powder material also include a small amount of A salt and nano-oxide M; wherein the molar percentage content of A salt is greater than 0 and less than 3%; the molar percentage content of nano-oxide M is greater than 0 and less than 25%;
[0011] Step 5, mixing the above-obtained undispersed nano-Si / Ge powder material with a solvent mainly composed of non-aqueous materials to form a slurry, and then ball milling or sand milling for a period of time in a ball mill or sand mill;
[0012] Step 6: The slurry obtained above is subjected to solid-liquid separation, and the solid powder material is collected to obtain a nano-Si / Ge powder material with good dispersibility; the nano-Si / Ge powder material is composed of a main component and a secondary component; the main component of the nano-Si / Ge powder material is nano-M, and its average component is mainly A x1 M y1 T z1 or A x3 M y3 T z3 , wherein 0<x1≤1%, 98.0%≤y1<100%, 0<z1<1.5%; 0<x3≤0.5%, 99%≤y3<100%, 0<z3<1%; x1, y1, z1, x3, y3, z3 represent the atomic percentage content of the corresponding constituent elements respectively; the A solid solution exists in the average composition mainly A x1 M y1 T z1 or A x3 M y3 T z3 The secondary components of the nano Si / Ge powder material include a small amount of A salt and nano M oxide; wherein the molar percentage content of the A salt is greater than 0 and less than 3%; the molar percentage content of the nano M oxide is greater than 0 and less than 25%; the particle size of the nano M oxide is less than 25nm; the particle size range of the nano M particles is 3nm to 500nm; the particle shape of the nano M is mainly at least one of spherical, nearly spherical, and short rods, and among the nano M particles, the volume percentage content of dendritic, branch-like, filamentous, and long rod-like (aspect ratio greater than 3) powder particles is less than 20%.
[0013] In the step 1,
[0014] Further, the initial alloy raw material containing T-type elements includes at least one of bulk A, bulk M, and bulk AM alloy;
[0015] Further, the initial alloy raw material containing T-type elements includes at least one of A ingot, M ingot and AM ingot;
[0016] For example, when A is mainly Al, the A ingot is mainly Al ingot; when M is mainly Si, the M ingot is mainly Si ingot; when M is mainly Si-Ge alloy, the M ingot is mainly Si-Ge ingot; when A is mainly Al and M is mainly Si, the AM ingot is mainly Al-Si ingot;
[0017] Further, the initial alloy raw material containing T-type elements includes Si ingots, and at least one of Al ingots or Zn ingots, and the atomic percentage content of T-type elements in the initial alloy raw material is higher than 0.01%;
[0018] Furthermore, the atomic percentage content of T-type elements in the initial alloy raw material is higher than 0.05%;
[0019] Furthermore, the atomic percentage content of T-type elements in the initial alloy raw material is higher than 0.1%;
[0020] Furthermore, the T-type element includes at least one of Fe, Cu, Mn, Mg and Ca;
[0021] Note: Generally speaking, cheap industrial Al ingots contain T-type impurity elements such as Fe, Cu, Mn, and Mg, while cheap industrial silicon ingots contain T-type impurity elements such as Fe and Ca.
[0022] Furthermore, the A comprises at least one of Zn and Al;
[0023] Further, the A mainly comprises Zn;
[0024] Further, the A mainly comprises Al;
[0025] Further, 75%≤a<99.39%, 0.6%<b<24.99%, 0.01%<d≤7.5%;
[0026] Further, 80%≤a<94.95%, 5%≤b<19.95%, 0.05%<d≤5%;
[0027] Further, 80%≤a<91.95%, 8%≤b<19.95%, 0.05%<d≤5%;
[0028] Further, when the A is mainly Al, the atmosphere of the initial alloy melting is an atmospheric environment;
[0029] Furthermore, when the Al content in the A is more than 80%, the atmosphere for melting the initial alloy is the atmospheric environment;
[0030] Furthermore, when the Zn content in A is more than 20%, the initial alloy is melted in a negative pressure protective atmosphere or in a positive pressure closed container;
[0031] Furthermore, when the Zn content in A is more than 20%, the initial alloy is melted in a positive pressure closed container;
[0032] Note: Since Zn is easy to volatilize and oxidize, it needs to be melted in a negative pressure protective atmosphere or in a positive pressure closed container; the positive pressure means that the internal pressure of the container containing the alloy is higher than one atmosphere when the alloy is melted.
[0033] Furthermore, the volume of the alloy melt in the positive pressure closed container accounts for more than 20% of the volume of the positive pressure closed container;
[0034] Furthermore, the volume of the alloy melt in the positive pressure closed container accounts for more than 50% of the volume of the positive pressure closed container;
[0035] Furthermore, the volume of the alloy melt in the positive pressure closed container accounts for more than 75% of the volume of the positive pressure closed container;
[0036] Furthermore, the volume of the alloy melt in the positive pressure closed container accounts for more than 95% of the volume of the positive pressure closed container;
[0037] When the volume of the alloy melt in the positive pressure closed container accounts for a considerable proportion, or even the vast majority or all, of the volume of the positive pressure closed container, the influence of melt oxidation or melt volatilization can be ignored, and it is only necessary to ensure the pressure resistance of the container. This greatly simplifies the smelting process of the initial alloy with a high Zn content.
[0038] Furthermore, the positive pressure source includes at least one of high temperature air pressure, high pressure air pressure, hydraulic pressure, and mechanical pressure.
[0039] In the step 2,
[0040] Furthermore, the rapid solidification technology includes at least one of melt stripping, melt pulling, melt jet water quenching, gas atomization condensation, water atomization condensation, and water vapor combined atomization condensation;
[0041] The melt stripping method includes: flowing or shooting the initial alloy melt onto one or more high-speed rotating roller surfaces, and then the alloy melt is spun into a strip-shaped or belt-shaped rapid-solidification alloy by the high-speed rotating roller surfaces; further, the rollers are mainly composed of metal; further, the rollers mainly contain copper;
[0042] Preferably, the thickness of the quick-setting alloy strip is in the range of 10 μm to 1 mm;
[0043] As a further preferred embodiment, the thickness of the quick-setting alloy strip is in the range of 10 μm to 200 μm;
[0044] As a further preferred embodiment, the thickness of the quick-setting alloy strip is in the range of 10 μm to 100 μm;
[0045] As a further preferred embodiment, the thickness of the quick-setting alloy strip is in the range of 10 μm to 50 μm;
[0046] As a further preference, the thickness of the quick-setting alloy strip is in the range of 10 μm to 25 μm.
[0047] The melt drawing process involves cutting the melt surface through a high-speed rotating metal conical roller to bring out a wire-shaped or ribbon-shaped quick-solidifying alloy;
[0048] The melt jet water quenching: the initial alloy melt is ejected from a positive pressure closed container containing the alloy melt through one or more holes under the action of gravity or pressure, and is further ejected into water for quenching and cooling. The shape of the rapidly solidified alloy cooled by the melt jet water quenching is at least one of irregular strips, irregular filaments, irregular blocks, and irregular particles;
[0049] Furthermore, the actual process of melt jet water quenching includes melt jet gas quenching process. For example, when the melt jets out from the positive pressure closed container and has not yet come into contact with water, the jet actually comes into contact with air, which is the melt jet gas quenching process.
[0050] The melt jet water quenching method does not require complicated melt rapid solidification equipment, and can directly inject the alloy melt from a positive pressure closed container into water under pressure through multiple jet holes for cooling, thereby greatly improving production efficiency.
[0051] Further, the average pore size of the jet hole is 1 μm-2 mm; further, the average pore size of the jet hole is 5 μm-500 μm; further, the average pore size of the jet hole is 5 μm-200 μm; further, the average pore size of the jet hole is 5 μm-100 μm;
[0052] Further, the diameter of the quick-setting alloy obtained by the melt jet water quenching is 1 μm-2 mm; further, the diameter of the quick-setting alloy obtained by the melt jet water quenching is 5 μm-500 μm; further, the diameter of the quick-setting alloy obtained by the melt jet water quenching is 5 μm-200 μm; further, the diameter of the quick-setting alloy obtained by the melt jet water quenching is 5 μm-100 μm;
[0053] Further, the number of jet holes corresponding to the positive pressure closed container exceeds 2; further, the number of jet holes corresponding to the positive pressure closed container exceeds 10; further, the number of jet holes corresponding to the positive pressure closed container exceeds 100; further, the number of jet holes corresponding to the positive pressure closed container exceeds 10,000;
[0054] Furthermore, the pressure of the melt at the jet hole is greater than 0.05 MPa (one standard atmospheric pressure is 0.1 MPa);
[0055] Furthermore, the pressure of the melt at the jet hole is greater than 1 MPa;
[0056] Furthermore, the pressure of the melt at the jet hole is greater than 10 MPa;
[0057] The pressure in the positive pressure closed container can be adjusted and varied during the alloy smelting process and the alloy jetting process.
[0058] Furthermore, the water used for the melt jet water quenching cooling is water flowing at a high speed under stirring;
[0059] Note: High-speed flowing water under stirring can ensure that the bubbles generated during the quenching process are quickly taken away, thereby improving the quenching efficiency.
[0060] Furthermore, the water used for quenching is flowing living water, which can take away the heat. After the water flows away and cools down, it flows back to participate in quenching; the quick-setting alloy obtained by quenching sinks to the bottom of the water and is easy to collect.
[0061] Furthermore, when the rapid solidification technology is mainly melt jet water quenching, the initial alloy melting condition is positive pressure closed container melting.
[0062] The gas atomization condensation: the melt flows out or ejects from the container containing the alloy melt, and is atomized and condensed by a high-speed airflow; the shape of the quick-setting alloy obtained by the gas atomization condensation is mainly at least one of a nearly spherical shape and a water drop shape;
[0063] The water atomization condensation: the melt flows out or ejects from the container containing the alloy melt, and is atomized and condensed by a high-speed water flow; the shape of the quick-setting alloy obtained by the water atomization condensation is mainly at least one of a nearly spherical shape, a water drop shape, and a dumbbell shape;
[0064] The water vapor combined atomization condensation: the melt flows out or ejects from the container containing the alloy melt, and is atomized and condensed by high-speed water flow and air flow at the same time; the shape of the quick-setting alloy obtained by the water vapor combined atomization condensation is mainly at least one of a nearly spherical shape, a water drop shape, and a dumbbell shape;
[0065] In summary, the shape of the quick-setting alloy includes at least one of strip, ribbon, filament, irregular strip, irregular filament, irregular block, irregular granular, nearly spherical, teardrop, and dumbbell;
[0066] Furthermore, the rapid solidification technology includes at least one of melt stripping and melt jet water quenching;
[0067] Furthermore, the rapid solidification technology is mainly melt stripping;
[0068] Furthermore, the rapid solidification technology is mainly melt jet water quenching;
[0069] Furthermore, the melt cooling rate corresponding to the rapid solidification technology is 10 3 K / s-10 8 K / s;
[0070] Furthermore, the melt cooling rate corresponding to the rapid solidification technology is 10 4 K / s-10 8 K / s;
[0071] Furthermore, the melt cooling rate corresponding to the rapid solidification technology is 10 4 K / s-10 6 K / s;
[0072] Furthermore, the melt cooling rate corresponding to the rapid solidification technology is 10 5 K / s-10 8 K / s;
[0073] Further, the particle size range of the dispersed particle phase is 3nm to 500nm; further, the particle size range of the dispersed particle phase is 3nm to 200nm; further, the particle size range of the dispersed particle phase is 3nm to 120nm; further, the particle size range of the dispersed particle phase is 3nm to 100nm; further, the particle size range of the dispersed particle phase is 3nm to 75nm.
[0074] Generally speaking, the higher the melt cooling rate corresponding to the rapid solidification technology, the smaller the particle size of the corresponding dispersed particles;
[0075] Further, the particle shape of the dispersed particle phase includes at least one of dendritic, branch-like, spherical, nearly spherical, filamentous, and rod-like;
[0076] Furthermore, among the dispersed particles, the volume percentage of dendrite-shaped, branch-shaped, filament-shaped, and long rod-shaped (with an aspect ratio greater than 3) particles in all dispersed particles exceeds 20%;
[0077] Furthermore, among the dispersed particles, the volume percentage of dendrite-shaped, branch-shaped, filament-shaped, and long rod-shaped (with an aspect ratio greater than 3) particles in all dispersed particles exceeds 30%;
[0078] Since the growth of dispersed particles in the rapid solidification alloy does not occur in the form of uniform growth of spherical particles, but mainly in the form of dendritic, dendrite, filament, and long rod particles extending and growing in a certain direction, even if the dispersed particles grow (the length of the branches or ligaments becomes longer), the increase in the diameter of the branches or ligaments of the dendritic, dendrite, filament, and long rod particles is still small. This feature provides a prerequisite for breaking and crushing them in a short time by using cheap coarse grinding beads in the subsequent sanding process.
[0079] When the dispersed particles are in at least one of the shapes of dendrites, branches, filaments, and rods, the particle size of the dispersed particles specifically refers to the diameter of the cross section of the branches, filaments, and rods.
[0080] Furthermore, the volume percentage of the dispersed particle phase in the corresponding rapid-solidifying alloy is less than 50%.
[0081] Furthermore, the volume percentage of the dispersed particle phase in the corresponding rapid-solidifying alloy is less than 30%.
[0082] The volume percentage of the dispersed particle phase in the rapid solidification alloy is related to the composition of the initial alloy melt. The higher the M content in the initial alloy melt, the higher the volume percentage of the dispersed particle phase in the rapid solidification alloy.
[0083] Description: Generally speaking, industrial Al ingots contain impurity elements such as Fe, Cu, Mn, and Mg, while industrial silicon ingots contain impurity elements such as Fe and Ca. During the solidification process of the initial alloy melt, the T-type elements in the initial alloy melt are redistributed in the dispersed particle phase and the matrix phase, and are enriched in the matrix phase, and the T-type elements in the dispersed particle phase are depleted, that is, the dispersed particle phase with significantly reduced T-type element content can be obtained through the initial alloy raw material containing a higher T-type element, thereby achieving the purification of the dispersed particle phase, which has a positive significance.
[0084] In the rapidly solidified alloy, the average composition of the dispersed particle phase is mainly A x1 M y1 Tz1 , and the A element therein exists as a solid solution in the dispersed particle phase; the average composition of the matrix phase is mainly A x2 M y2 T z2 , and the M element exists in the matrix phase in solid solution; that is, the A atoms exist mainly in the form of solid solution atoms, with the average composition mainly being A x1 M y1 T z1 The M atoms are mainly present in the dispersed particle phase with an average composition of A in the form of solid solution atoms. x2 M y2 T z2 in the matrix phase.
[0085] Furthermore, the solid solution method includes at least one of interstitial solid solution and substitutional solid solution;
[0086] Further, 0<x1≤0.5%, 98.5%≤y1<100%, 0<z1<1.5%;
[0087] Further, 0<xl≤0.5%, 99%≤y1<100%, 0<z1<1.0%;
[0088] Further, 81%≤x2<99.8%, 0.2%<y2<2%, 0<z2<18.8%;
[0089] Further, 81%≤x2<99.5%, 0.5%<y2<2%, 0<z2<18.5%;
[0090] Furthermore, 2z1<z2; preferably, 3z1<z2.
[0091] In the step three,
[0092] Further, the acid includes at least one of hydrochloric acid, nitric acid, sulfuric acid, and phosphoric acid;
[0093] Furthermore, the reaction process between the matrix phase in the rapid-setting alloy and the acid solution includes: the A element in the matrix phase of the rapid-setting alloy is mainly dissolved by the acid solution to become the corresponding A salt solution, the T-type elements are mainly dissolved into T salt solution, and the M element dissolved in the matrix phase of the rapid-setting alloy is converted into M acid or nano-oxide M; when M is Si, the nano-oxide M is nano-silicon dioxide.
[0094] For example, when A is Al, the Al element in the quick-setting alloy matrix phase is mainly dissolved by the acid solution to become a corresponding Al salt solution; when T is Fe, Fe is mainly dissolved to become a Fe salt solution.
[0095] Explanation: Since the M element dissolved in the matrix phase of the quick-setting alloy exists in the matrix phase in the form of M atoms, when the matrix phase is dissolved by acid reaction, the M atoms that are not easy to react with acid immediately are released. The single M atom has a very high specific surface area and is easily oxidized by the oxygen element in the solution to become nano-oxidized M, or easily undergoes hydrogen evolution and hydrolysis reaction with water in the reaction solution (the chemical equation for the reaction of silicon atoms and water to generate silicic acid and hydrogen is: Si+4H2O=H4SiO4+2H2↑, where H4SiO4 is silicic acid). Therefore, the M (M is at least one of Si and Ge) atoms dissolved in the matrix phase are mainly hydrolyzed or oxidized. This part of the M element cannot eventually become an effective component of the nano-M powder material.
[0096] The nano-oxide M includes at least one of nano-oxide Si, nano-oxide Ge, and nano-oxide Si / Ge;
[0097] Further, the nano-oxidation M is mainly amorphous; further, the nano-oxidation M is flocculent;
[0098] Furthermore, the particle size of the nano-oxidation M is less than 25 nm; further, the particle size of the nano-oxidation M is less than 5 nm; Note: the particle size is the diameter of the corresponding filament or ligament of the filamentous structure.
[0099] Furthermore, during the reaction between the quick-setting alloy and the acid solution, the dispersed particle phase mainly composed of the M element is not easy to react with the acid solution, and the dispersed particle phase can be freely separated from the quick-setting alloy when the matrix phase is mainly dissolved. The free separation means that after the matrix phase is removed, the dispersed particle phase can be separated from the original quick-setting alloy and move freely to form a solid component in the slurry, that is, a nano-M powder material.
[0100] Furthermore, the particle size of the nano M powder material mainly composed of the original dispersed particles is at least several nanometers, or tens of nanometers, so its specific surface area is much higher than that of a single M atom. Although the M atoms on the particle surface of the nano M powder material mainly composed of the original dispersed particles will also undergo oxidation or hydrogen evolution hydrolysis in the reaction solution; after reaching the reaction equilibrium, the surface of the nano M powder particles will be passivated (for example, an oxide M protective film will be formed), and further oxidation or hydrogen evolution hydrolysis will be greatly inhibited (but cannot be completely stopped). At this time, in addition to the passivation of the particles' surface atoms, the main component of the nano M powder material mainly composed of the original dispersed particles is still nano M, which is mainly composed of AMT and contains a small amount of A and T elements.
[0101] Furthermore, after the above step 2 and before step 3, a heat treatment process for the quick-setting alloy is added. This step is named step (2 / 3);
[0102] Step (two / three): heat treating the rapidly solidified alloy obtained in step two.
[0103] Further, the heat treatment temperature of the quick-setting alloy is 150°C-550°C; further, the heat treatment temperature of the quick-setting alloy is 150°C-500°C; further, the heat treatment temperature of the quick-setting alloy is 200°C-450°C; further, the heat treatment temperature of the quick-setting alloy is 250°C-450°C.
[0104] Furthermore, the heat treatment time of the quick-setting alloy is 1h-240h; further, the heat treatment time of the quick-setting alloy is 1h-48h; further, the heat treatment time of the quick-setting alloy is 1h-24h.
[0105] Generally speaking, the lower the heat treatment temperature is, the longer the heat treatment time is required, and the better the effect of reducing the content of solid solution M in the matrix phase is.
[0106] Furthermore, the heat treatment process for the rapid-setting alloy aims to reduce the content of the M element existing in solid solution in the matrix phase of the rapid-setting alloy.
[0107] Since the quick-setting alloy is formed by rapid solidification, about 2% of the M element can be dissolved in its matrix phase (the corresponding solid solution equilibrium temperature is about 570°C); and this part of the M element is either oxidized or hydrolyzed after contacting the reaction solution in the form of M atoms, and is essentially lost.
[0108] According to the characteristic that the equilibrium solid solubility of M element in the matrix phase of the rapid solidifying alloy decreases with decreasing temperature (e.g., the equilibrium solid solubility of M in the matrix phase at room temperature is about 0.05%), when the rapid solidifying alloy is heat treated at a temperature below 570°C, its saturated solid solubility decreases, and part of the M element will precipitate from the matrix phase in the form of M-containing dispersed precipitate phase through diffusion aggregation. The particle size of the M-containing dispersed precipitate phase can be several nanometers or tens of nanometers, and its composition and properties are similar to those of the dispersed particles originally existing in the rapid solidifying alloy.
[0109] Therefore, when the heat treatment temperature is lower, more M-containing dispersed particle phases can be precipitated, thereby increasing the total content of M-containing dispersed particle phases in the rapid-solidifying alloy and significantly reducing the loss of M element, which has positive significance.
[0110] Furthermore, after the heat treatment, the solidified structure of the rapid solidification alloy includes a matrix phase after the heat treatment, a dispersed particle phase after the heat treatment, and a newly precipitated dispersed particle phase.
[0111] Furthermore, according to the phase equilibrium principle, the average composition of the dispersed particle phase after heat treatment (including the original dispersed particle phase and the newly precipitated dispersed particle phase) is mainly A x3 My3 T z3 ; The average composition of the matrix phase after heat treatment is mainly A x4 M y4 T z4 ; Wherein, 0<x3≤0.5%, 98.5%≤y3<100%, 0<z3<1%; 81%≤x4<99.98%, 0.02%<y4<1.5%, 0<z4<18.98%; Wherein, x3, y3, z3, x4, y4, z4 represent the atomic percentage content of the corresponding constituent elements respectively; The A solid solution exists in the average composition mainly A x3 M y3 T z3 In the dispersed particle phase, the M solid solution exists in the average composition mainly A x4 M y4 T z4 in the matrix phase;
[0112] Further, 0.02%<y4<1%, further, 0.02%<y4<0.5%, further, 0.03%<y4<0.3%;
[0113] Furthermore, x3<x1, that is, the A content in the dispersed particle phase will be further reduced by heat treatment;
[0114] Furthermore, z3<z1; that is, the content of T-type elements in the dispersed particle phase will be further reduced through heat treatment;
[0115] Furthermore, y1<y3, that is, the content of M in the dispersed particle phase will be further increased by heat treatment;
[0116] Furthermore, y4<y2, that is, the content of M in the matrix phase will be further reduced by heat treatment;
[0117] Furthermore, x2<x4, that is, the content of A in the matrix phase will be further increased by heat treatment;
[0118] Furthermore, z2<z4, that is, the content of T-type elements in the matrix phase will be further increased through heat treatment;
[0119] After step (ii / iii), the yield of the nano-M powder material in the subsequent step 3 is significantly improved, and at the same time, the content of the T-type elements in the nano-M powder material is further reduced, which has positive significance.
[0120] In the step 4,
[0121] Furthermore, the solid-liquid separation method includes at least one of sedimentation solid-liquid separation, flotation solid-liquid separation, centrifugal solid-liquid separation, and filtration solid-liquid separation;
[0122] Sedimentation solid-liquid separation: Since the density of the nano M is greater than the density of the salt solution in the solid-liquid mixture, it can settle to the bottom of the container, thereby achieving preliminary solid-liquid separation;
[0123] Bubble-float solid-liquid separation: Since a small amount of M element dissolved in the quick-setting alloy will become ultra-fine flocculent oxide M in the reaction solution, it has the effect of a foaming agent and will entrain a certain amount of bubbles and a part of nano-scale nano-M and float on the surface of the salt solution. Therefore, the initial separation of part of the nano-M and the salt solution can be achieved by collecting the foam containing nano-M particles floating on the surface of the salt solution;
[0124] Centrifugal solid-liquid separation: For nano-M suspended in salt solution, or nano-M slurry with high solid content, preliminary solid-liquid separation can be achieved by centrifugation;
[0125] Filtration solid-liquid separation: The centrifugal solid-liquid separation process can be combined with filter cloth or filter bag to further promote this solid-liquid separation by filtration.
[0126] The above-mentioned solid-liquid separation methods can be combined and used repeatedly. At the same time, repeated washing with fresh solvents can be used to perform repeated solid-liquid separation to obtain nano-M powder materials with as little salt residue as possible.
[0127] Furthermore, the solid-liquid separation method includes flotation solid-liquid separation;
[0128] Furthermore, the solvent is at least one of water, ethanol and methanol;
[0129] Furthermore, in the process of repeatedly washing the obtained solid product, an appropriate amount of hydrofluoric acid is added to the washing liquid in the early washing process. The amount of hydrofluoric acid added is based on the ability to significantly remove the ultrafine nano-oxide M in the solid product, while ensuring that the nano-oxide M with a particle size much larger than the ultrafine nano-oxide M is not significantly corroded; after the later washing process, the F salt (fluorine-containing salt) generated after the addition of hydrofluoric acid is also substantially removed.
[0130] Further, the concentration of the hydrofluoric acid is below 0.1 mol / L; further, the concentration of the hydrofluoric acid is below 0.01 mol / L;
[0131] Description: Ultrafine nano-oxidized M is mainly derived from the M element dissolved in the matrix phase of the rapid-setting alloy during the reaction between the rapid-setting alloy and the acid.
[0132] Furthermore, the step 4 obtains a powder material of nano-Si / Ge that has not been dispersed, the main component of which is nano-M with passivated particle surface, and the secondary components also include a small amount of A salt and nano-oxidation M; wherein the molar percentage content of A salt is greater than 0 and less than 3%; the molar percentage content of nano-oxidation M is greater than 0 and less than 25%;
[0133] Furthermore, the molar percentage content of the A salt is greater than 0.01% and less than 2%;
[0134] Furthermore, the molar percentage content of the A salt is greater than 0 and less than 1%;
[0135] Furthermore, the molar percentage content of the nano-oxide M is greater than 0.1% and less than 20%;
[0136] Furthermore, the molar percentage content of the nano-oxide M is greater than 0.5% and less than 15%;
[0137] The molar percentage content of salt A refers to the molar percentage of salt A in the entire undispersed nano-Si / Ge powder material;
[0138] The more the A salt concentration is reduced, the more washing times are required and the higher the process cost;
[0139] Furthermore, the A salt is the chloride of A, for example, when A is Al, its chloride is AlCl3.
[0140] The molar percentage content of nano-oxide M refers to the molar percentage of nano-oxide M in the entire undispersed nano-Si / Ge powder material;
[0141] The criterion for judging the passivation of the particle surface is whether the particle releases hydrogen obviously when in contact with water. If the particle cannot release hydrogen obviously, the particle surface is passivated.
[0142] Furthermore, the particle shape of the nano-M includes at least one of dendrite, branch, spherical, nearly spherical, filamentous, and rod-shaped;
[0143] Furthermore, among the nano M particles, the volume percentage of dendrites, branches, filaments, and long rods (with an aspect ratio greater than 3) in all nano M particles exceeds 20%;
[0144] Furthermore, among the nano M particles, the volume percentage of dendrites, branches, filaments, and long rods (with an aspect ratio greater than 3) in all nano M particles exceeds 30%;
[0145] Note: Since the shapes of nano M particles include a large number of dendrites, branches, filaments, and long rods, the nano M obtained in step 4 is easy to hook up and agglomerate together. In addition, a small amount of flocculent nano oxygen M in the undispersed nano Si / Ge powder material is also easy to aggregate the nano M together like a net.
[0146] However, the above agglomeration is not the agglomeration of all particles, but the agglomeration of particles with a considerable content (such as more than 30% by volume). The criterion for judging agglomeration is whether the static slurry has obvious sedimentation and stratification in a short time. If the static slurry with high concentration (solid content 10%) has obvious stratification within 2 hours, it is an obvious agglomeration.
[0147] In the step five,
[0148] If the solvent used for cleaning in step 4 contains water, the undispersed nano-Si / Ge powder material obtained after the desalting and cleaning in step 4 may also contain water. Therefore, the moisture in the undispersed nano-Si / Ge powder material needs to be dried and removed before making the slurry. The drying method includes at least one of spray drying, oven drying, vacuum drying, and natural drying.
[0149] If the solvent used in step 4 for washing does not contain water, drying is not necessary before making the slurry;
[0150] Note: Fresh surface atoms of ultrafine nano-M particles will react with water to generate hydrogen, and may also be oxidized to form nano-M oxide with a foaming effect; although the surface atoms of nano-M particles have been largely passivated before ball milling / sand milling, the passivated surface of nano-M particles is destroyed during ball milling / sand milling, and fresh M surface atoms are constantly exposed. If there is water in the slurry in wet ball milling / sand milling, it will react with the M atoms on the surface of the nano-M particles and continuously produce hydrogen. In addition, the foaming effect of nano-M oxide will cause the slurry to foam and expand, making it impossible for the slurry that should circulate in the wet ball mill / sand mill to circulate normally. Therefore, the water content in the slurry for ball milling / sand milling needs to be strictly controlled.
[0151] The solvent in the slurry includes the solvent of the undispersed nano-Si / Ge powder material (i.e. the solvent without drying) and the solvent added later;
[0152] Furthermore, the water content that is inevitably introduced into the solvent that is mainly composed of non-aqueous substances is less than 15% by volume in the entire slurry solvent;
[0153] Furthermore, the water content inevitably introduced into the solvent mainly composed of non-aqueous substances is less than 5% by volume in the entire slurry solvent;
[0154] Furthermore, the water content that is inevitably introduced into the solvent that is mainly composed of non-aqueous substances is less than 1% by volume in the entire slurry solvent;
[0155] Note: The unavoidable introduction of moisture includes at least one of the following: introduction of atmospheric moisture and introduction of insufficient purity of the solvent itself;
[0156] Furthermore, the solvent mainly composed of non-aqueous solvent is mainly composed of organic solvent;
[0157] Furthermore, the solvent mainly composed of non-aqueous substances is mainly composed of organic solvents, and the content of the organic solvents exceeds 85%;
[0158] Furthermore, the solvent mainly composed of non-aqueous substances is mainly composed of ethanol, and the content of ethanol exceeds 85%;
[0159] Further, in the slurry, the volume content of the solvent is 60%-99%; further, in the slurry, the volume content of the solvent is 75%-95%; further, in the slurry, the volume content of the solvent is 85%-95%;
[0160] Furthermore, the grinding beads in the ball mill or sand mill are made of at least one of metal balls and ceramic balls;
[0161] Furthermore, the particle size of the grinding beads is 0.15 mm-5 mm; and ultra-expensive grinding beads with a particle size of 0.1 mm are not required.
[0162] Further, the particle size of the grinding beads is 0.25mm-5mm; further, the particle size of the grinding beads is 0.3mm-1mm;
[0163] Furthermore, the grinding beads in the ball mill or sand mill are mainly made of zirconium oxide beads;
[0164] Further, the particle size of the zirconia beads is 0.15mm-5mm; further, the particle size of the zirconia beads is 0.25mm-5mm; further, the particle size of the zirconia beads is 0.3mm-1mm;
[0165] According to the existing wet ball milling / sand milling process of silicon powder, in order to obtain nano silicon powder with an average particle size of less than 200nm, spherical zirconia beads with a particle size of less than 0.2mm must be used, and spherical zirconia beads with a particle size of 0.1mm are generally required. Since the price of zirconia beads with a particle size of less than 0.2mm (especially spherical zirconia beads with a particle size of 0.1mm must be imported) is 5-10 times that of zirconia beads with a particle size of 0.3mm and above, the present application does not need to use extremely expensive ultrafine zirconia beads, which has extremely high market significance.
[0166] Description: The purpose of ball milling / sand milling in this application is to: 1) disperse the agglomerated nano M particles in the slurry; 2) break the nano M dendritic, branch-like, filamentous, and long rod-like particles in the slurry into short rod-like particles or nearly spherical particles; 3) obtain a fresh nano M particle surface (remove the original passivation layer).
[0167] Since the function of the grinding beads in this application is mainly to disperse the particles rather than to crush the large spherical particles, expensive ultrafine zirconia beads are not required.
[0168] Since the growth of dispersed particles in the rapid solidification alloy does not occur in the form of uniform growth of spherical particles, but mainly in the form of dendritic, dendrite, filament, and long rod particles extending and growing in a certain direction, even if the dispersed particles grow (the length of the branches or ligaments becomes longer), the increase in the diameter of the branches or ligaments of the dendritic, dendrite, filament, and long rod particles is still small. This feature provides a prerequisite for breaking and crushing them in a short time by using cheap coarse grinding beads during the sanding process.
[0169] As for the nano-M dendritic, tree-like, filamentous, and long rod-like particles in the slurry, it is much easier to break them into short rod-like particles or nearly spherical particles than to break large spherical particles. Large-particle zirconia beads for dispersion can be used.
[0170] The nano-M dendritic, branch-like, filamentous, and long rod-like particles originate from the dispersed particle phase in the rapid-solidification alloy.
[0171] Therefore, the present application only needs to use extremely low-priced large-particle zirconia beads (such as zirconia beads larger than 0.3 mm), and when large-particle zirconia beads are used, the wear loss of the particles is also greatly reduced, further reducing the cost.
[0172] Further, the ball milling / sand milling time is 1 min-10 h; further, the ball milling / sand milling time is 1 min-2 h; further, the ball milling / sand milling time is 1 min-1 h; further, the ball milling / sand milling time is 1 min-30 min;
[0173] Note: Since the main purpose of ball milling / sand milling is to disperse and break the nano-M dendrites, branches, filaments, and long rods into short rods or nearly spherical particles, and large-particle zirconium oxide beads are used. Therefore, the above purpose can be achieved in a short time, such as within 30min-1h. For the wet ball milling / sand milling process of traditional nano silicon powder, firstly, the silicon ingot needs to be ball milled for several hours to obtain coarse silicon powder with a particle size of about 5μm, and then the coarse silicon powder with a particle size of about 5μm is sand milled with large-particle zirconium oxide beads (particle size 0.5mm-1mm) for 5-10h to obtain medium-particle silicon powder with a particle size of 500nm, and finally the medium-particle silicon powder with a particle size of 500nm is sand milled with imported ultrafine zirconium oxide beads (particle size 0.1mm, small particle size, easy to wear and tear failure) for 5-10h to obtain fine nano silicon powder with a particle size of 120-200nm. Ultrafine nano-silicon powder below 120nm requires twice the time and loss cost to obtain, which is extremely expensive and difficult to mass produce.
[0174] Therefore, in the process of preparing well-dispersed nano-Si / Ge powder materials in the present application, the powder refinement process is cleverly completed in the process of forming dispersed particles (the higher the cooling rate, the finer the dispersed particles), and the above-mentioned ball milling / sand milling only goes through the dispersion process and the length breaking process of long particles in the powder preparation process, which greatly reduces the time cost and loss cost of the entire process.
[0175] Furthermore, the ball milling / sand milling process is a separate sand milling process, that is, the powder slurry is dispersed and the dendritic, dendrite-like, filamentous, and long rod-like particles are broken directly through the sand milling process, and the whole process does not require a ball milling process.
[0176] In step six,
[0177] The solid-liquid separation method includes at least one of spray drying, oven drying, vacuum drying and natural drying.
[0178] Furthermore, the solid-liquid separation process is carried out under a protective atmosphere;
[0179] Furthermore, during the spray drying process, the dry powder obtained by solid-liquid separation is protected by inert gas to prevent oxidation in contact with the atmosphere, while the solvent is recovered; the obtained dry powder is a well-dispersed nano-Si / Ge powder material.
[0180] The nano Si / Ge powder material is composed of a main component and a secondary component;
[0181] The main component of the nano Si / Ge powder material is nano M, and its average composition is mainly A x1 M y1 T z1 or A x3 M y3T z3 (The case of heat treatment of quick-setting alloy), wherein 0<x1≤1%, 98.0%≤y1<100%, 0<z1<1.5%; 0<x3≤0.5%, 98.5%≤y3<100%, 0<z3<1%; x1, y1, z1, x3, y3, z3 represent the atomic percentage content of the corresponding constituent elements respectively; the T-type element comprises at least one of Fe, Cu, Mn, Mg, Ca, Cd, M comprises at least one of Si and Ge, A comprises at least one of Zn, Sn, Pb, Ga, In, Ag, Bi, Al; the A solid solution exists in the average composition mainly of A x1 M y1 T z1 or A x3 M y3 T z3 of nano-M;
[0182] Further, the particle size range of the nano M particles is 3nm to 1μm; further, the particle size range of the nano M particles is 3nm to 500nm; further, the particle size range of the nano M particles is 3nm to 200nm; further, the particle size range of the nano M particles is 3nm to 120nm; further, the particle size range of the nano M particles is 3nm to 100nm; the particle size range of the nano M particles is 3nm to 75nm;
[0183] Furthermore, the particle shape of the nano-M is mainly at least one of spherical, nearly spherical, and short rod-shaped;
[0184] Note: Since the obtained powder has undergone ball milling / sand milling, the content of a small number of easily broken dendritic, branch-like, filamentous, and long rod-like (aspect ratio greater than 3) powders in the powder is very small;
[0185] Furthermore, in the nano M particles, the volume percentage of the powder particles in the form of dendrites, branches, filaments, and long rods (with an aspect ratio greater than 3) is less than 20%;
[0186] Furthermore, in the nano M particles, the volume percentage of the powder particles in the form of dendrites, branches, filaments, and long rods (with an aspect ratio greater than 3) is less than 10%.
[0187] Furthermore, in the nano M particles, the volume percentage of the powder particles in the form of dendrites, branches, filaments, and long rods (with an aspect ratio greater than 3) is less than 5%.
[0188] Furthermore, the nano M particles are nano M particles with high surface activity. Because they have undergone the ball milling / sand milling process, as long as the subsequent waterproofing and anti-oxidation measures are appropriate, the obtained nano M powder particles have a large amount of fresh surface and improved activity.
[0189] The nano M particles firstly originate from the dispersed particle phase in the quick-setting alloy, and when the quick-setting alloy undergoes heat treatment, they also originate from the dispersed precipitation phase precipitated from the matrix phase of the quick-setting alloy during the heat treatment process; then, in the process of the quick-setting alloy reacting with the acid, the dispersed particle phase or the dispersed precipitation phase in the quick-setting alloy falls off freely, forming the nano M particles whose particle surfaces in the slurry are roughly passivated, which are mainly the nano M particles that have not been dispersed. Then, after washing, the slurry is made again with a non-aqueous solvent, and the dispersed nano M particles are obtained through a ball milling / sand milling process, and at the same time, the dendritic, branch-like, filamentous, and long rod-like particles in the slurry are broken into short rod-like particles or nearly spherical particles, and a fresh nano M surface is obtained (the original passivation layer is removed).
[0190] The secondary components of the nano Si / Ge powder material include a small amount of A salt and nano oxide M;
[0191] Furthermore, due to the high specific surface area of nano M particles, the residual A salt on the surface is difficult to be thoroughly cleaned. Therefore, the prepared nano Si / Ge powder material, in addition to nano M, also contains a small amount of A salt, such as the salts corresponding to Zn and Al: ZnCl2, AlCl3, Al(NO3)3.
[0192] Furthermore, in the prepared nano-Si / Ge powder material, the molar percentage content of the A salt is greater than 0 and less than 3%;
[0193] Furthermore, in the prepared nano-Si / Ge powder material, the molar percentage content of the A salt is greater than 0.01% and less than 2%;
[0194] Furthermore, in the prepared nano-Si / Ge powder material, the molar percentage content of the A salt is greater than 0 and less than 1%;
[0195] Furthermore, in the prepared nano-Si / Ge powder material, the molar percentage content of the A salt is greater than 0 and less than 0.5%.
[0196] Furthermore, the A salt is the chloride of A, for example, when A is Al, its chloride is AlCl3.
[0197] Furthermore, the prepared nano-Si / Ge powder material contains a small amount of nano-oxide M; when M is Si, the nano-oxide M is nano-SiO2.
[0198] Description: The nano-oxidized M mainly comes from two sources: a) the M element dissolved in the quick-setting alloy matrix phase is converted into nano-oxidized M. Since it is solid, it enters the M-containing powder material during the solid-liquid separation process; b) before the sand / ball milling treatment, the surface of the M powder material particles is passivated to form an oxidized M protective film, which is peeled off during the sand / ball milling process. Since it is solid, it enters the finally prepared nano-Si / Ge powder material during the solid-liquid separation process in step six.
[0199] Further, the nano-oxidation M is mainly amorphous; further, the nano-oxidation M is flocculent;
[0200] Further, the particle size of the nano-oxidation M is less than 25 nm; further, the particle size of the nano-oxidation M is less than 15 nm; further, the particle size of the nano-oxidation M is less than 5 nm;
[0201] Note: The particle size of the nano-oxidation M is the diameter of the corresponding filament or ligament of the nano-oxidation M filament flocculent structure.
[0202] In summary, the nano Si / Ge powder material is composed of a main component and a secondary component; the main component of the nano Si / Ge powder material is nano M, and its average composition is mainly A x1 M y1 T z1 or A x3 M y3 T z3 (The case where the quick-setting alloy has undergone heat treatment), the secondary components of the nano-Si / Ge powder material include a small amount of A salt and nano-oxide M; wherein the molar percentage content of the A salt is greater than 0 and less than 3%; the molar percentage content of the nano-oxide M is greater than 0 and less than 25%;
[0203] Furthermore, the molar percentage content of the A salt is greater than 0.01% and less than 2%;
[0204] Furthermore, the molar percentage content of the A salt is greater than 0 and less than 1%;
[0205] Furthermore, the molar percentage content of the A salt is greater than 0 and less than 0.5%;
[0206] Furthermore, the molar percentage content of the nano-oxide M is greater than 0.1% and less than 20%;
[0207] Furthermore, the molar percentage content of the nano-oxide M is greater than 0.5% and less than 15%;
[0208] Furthermore, the molar percentage content of the nano-oxide M is greater than 0 and less than 10%;
[0209] Furthermore, the molar percentage content of the nano-oxide M is greater than 0 and less than 5%;
[0210] Furthermore, the molar percentage content of the nano-oxide M is greater than 0 and less than 2.5%.
[0211] The molar percentage content of the A salt refers to the molar percentage of the A salt in the entire nano-Si / Ge powder material;
[0212] The molar percentage content of the nano-oxide M refers to the molar percentage of the nano-oxide M in the entire nano-Si / Ge powder material;
[0213] The A solid solution exists in the average composition mainly A x1 M y1 T z1 or A x3 M y3 T z3 of nano-M;
[0214] Note: In the nano-Si / Ge powder material, the molar percentage content of the secondary component nano-oxide M is closely related to the two processing processes:
[0215] 1) After step 2 and before step 3, a heat treatment process for the quick-setting alloy is added, that is, after step (2 / 3), the M element existing in the solid solution in the matrix phase of the quick-setting alloy is reduced (see above), and the source of the M element that becomes nano-oxide M is reduced, thereby reducing the content of nano-oxide M in the final product.
[0216] 2) In the process of repeatedly washing the obtained solid product in step 4, an appropriate amount of hydrofluoric acid (see above) is added to the washing liquid in the previous washing process; the added hydrofluoric acid can remove the ultrafine nano-oxidation M in the solid product, thereby reducing the content of nano-oxidation M in the final product.
[0217] In the above two treatments, the treatment method 1) can precipitate most of the M element in the solid solution in the matrix phase of the rapid solidification alloy and transform it into dispersed precipitation phase particles containing M (the main component is A x3 M y3 T z3 ), thereby increasing the content of effective component nano M in nano Si / Ge powder materials, which has positive significance.
[0218] When at least one of the above two treatment processes is adopted, the molar percentage content of nano-oxide M in the nano-Si / Ge powder material is less than 5%.
[0219] When at least one of the above two processes is not adopted, the molar percentage content of nano-oxide M in the nano-Si / Ge powder material is higher than 5%.
[0220] illustrate:
[0221] Since Si has a solid solubility of about 2% in Al, and a solid solubility of Si in Zn is close to 0. Therefore, when M is mainly Si and A is mainly Zn, the solid solution of Si in the Zn-rich matrix phase of the rapid-setting alloy is also close to 0. At this time, the amount of nano-Si oxide that can be generated by the matrix phase of the rapid-setting alloy through acid reaction will be greatly reduced.
[0222] Furthermore, when M is mainly Si and A is mainly Zn, the nano-Si / Ge powder material with good dispersibility obtained in step six is mainly a nano-Si powder material with good dispersibility, wherein the molar percentage content of nano-Si oxide is greater than 0 and less than 5%; further, the molar percentage content of nano-Si oxide is greater than 0 and less than 2.5%.
[0223] Therefore, in terms of ultimately reducing the content of nano-silicon oxide in the nano-Si powder material, M is mainly Si and A is mainly Zn, which is a good alloy formula choice.
[0224] The present application also relates to a nano-Si / Ge-containing powder composite material, characterized in that:
[0225] The powder composite material containing nano-Si / Ge is composed of a main component and a secondary component; the main component of the powder composite material containing nano-Si / Ge is nano-M, and its average composition is mainly A x1 M y1 T z1 or A x3 M y3 T z3 , wherein 0<x1≤1%, 98.0%≤y1<100%, 0<z1<1.5%; 0<x3≤0.5%, 98.5%≤y3<100%, 0<z3<1%; x1, y1, z1, x3, y3, z3 represent the atomic percentage content of the corresponding constituent elements respectively; the T-type element comprises at least one of Fe, Cu, Mn, Mg, Ca, Cd, M comprises at least one of Si and Ge, A comprises at least one of Zn, Sn, Pb, Ga, In, Ag, Bi, Al; the A solid solution exists in the average composition mainly A x1 M y1 T z1 or A x3 M y3 T z3 of nano-M;
[0226] The secondary components of the nano-Si / Ge powder composite material include a small amount of A salt and nano-oxide M; wherein the molar percentage content of A salt is greater than 0 and less than 3%; the molar percentage content of nano-oxide M is greater than 0 and less than 25%;
[0227] Furthermore, the molar percentage content of the A salt is greater than 0.01% and less than 2%;
[0228] Furthermore, the molar percentage content of the A salt is greater than 0 and less than 1%;
[0229] Furthermore, the molar percentage content of the A salt is greater than 0 and less than 0.5%;
[0230] Furthermore, the molar percentage content of the nano-oxide M is greater than 0.1% and less than 20%;
[0231] Furthermore, the molar percentage content of the nano-oxide M is greater than 0.5% and less than 15%;
[0232] The molar percentage content of the A salt refers to the molar percentage of the A salt in the entire nano-Si / Ge-containing powder composite material;
[0233] The molar percentage content of the nano-oxide M refers to the molar percentage of the nano-oxide M in the entire nano-Si / Ge-containing powder composite material;
[0234] The A salt is the salt corresponding to the A element, such as the salt corresponding to Zn and Al: ZnCl2, AlCl3, Al(NO3)3;
[0235] The nano-oxide M includes at least one of nano-oxide Si (i.e. SiO2), nano-oxide Ge, and nano-oxide Si / Ge;
[0236] Further, the nano-oxidation M is mainly amorphous; further, the nano-oxidation M is flocculent;
[0237] Further, the particle size of the nano-oxidation M is less than 25 nm; further, the particle size of the nano-oxidation M is less than 5 nm. Further, the particle size of the nano-oxidation M is less than 5 nm.
[0238] Note: The particle size of the nano-oxidation M is the diameter of the corresponding filament or ligament of the nano-oxidation M filament flocculent structure.
[0239] Further, the particle size range of the nano M particles is 3nm to 500nm; further, the particle size range of the nano M particles is 3nm to 200nm; further, the particle size range of the nano M particles is 3nm to 120nm; further, the particle size range of the nano M particles is 3nm to 100nm; the particle size range of the nano M particles is 3nm to 75nm;
[0240] Furthermore, the particle shape of the nano M is mainly at least one of spherical, nearly spherical, and short rod-shaped, and the volume percentage of the powder particles of dendrite, branch, filament, and long rod (aspect ratio greater than 3) in the nano M particles is less than 20%;
[0241] Furthermore, the powder shape of the nano-M is mainly at least one of spherical, nearly spherical, and short rod-shaped, and the volume percentage of the powder particles of dendrite, branch, filament, and long rod (aspect ratio greater than 3) in the nano-M is less than 10%;
[0242] Furthermore, the nano-Si / Ge-containing powder composite material is prepared through steps 1 to 6 of the specification. For more details, see steps 1 to 6 of the specification.
[0243] The present application also relates to the application of the nano Si / Ge powder material or the powder composite material containing nano Si / Ge obtained by the preparation method of the above steps 1 to 6 in catalytic materials, powder metallurgy, composite materials, coatings, battery negative electrode materials, and silicon-carbon negative electrodes.
[0244] Through powder metallurgy, materials such as silicon carbide and silicon nitride can be prepared by sintering the nano-Si powder;
[0245] By applying it to battery negative electrode materials, the battery capacity and cycle times can be significantly improved.
[0246] The present application also relates to a method for preparing an undispersed nano Si / Ge powder material, which is characterized in that it is prepared by the preparation method including steps 1 to 4, and the details are described in steps 1 to 4 in the specification.
[0247] The creativity of this application mainly lies in the following aspects:
[0248] First, high-purity nano-Si / Ge powder materials can be prepared from low-purity raw materials. Generally speaking, industrial Al ingots contain T-type impurity elements such as Fe, Cu, Mn, and Mg, while industrial Si ingots contain T-type impurity elements such as Fe and Ca. This application can use cheap industrial Al ingots and Si / Ge ingots as initial alloy raw materials to obtain high-purity target nano-Si / Ge powder with reduced T-type impurity elements, which has positive significance.
[0249] Secondly, the melt jet water quenching method does not require complex melt rapid solidification equipment. The alloy melt can be directly injected into water under pressure through multiple jet holes for cooling, thus greatly improving production efficiency. Moreover, through the design of the jet aperture, such as when the jet aperture is designed to be 1μm-10μm, the alloy melt can also be ejected from the jet hole through pressure, thereby obtaining a rapid solidification alloy with a diameter of 1μm-10μm and rapidly cooled by water. Compared with the melt stripping, which can only obtain a minimum thickness of 15μm through a complex equipment system, the melt jet water quenching can achieve a higher cooling rate and obtain a finer dispersed particle phase in the rapid solidification alloy.
[0250] Third, by heat treating the quick-setting alloy, the content of the M element existing in the solid solution in the matrix phase of the quick-setting alloy is reduced, thereby increasing the yield of the M-containing powder material, and at the same time further reducing the content of the T-type elements in the M-containing powder material. Moreover, the content of the M element existing in the solid solution in the matrix phase of the quick-setting alloy is reduced due to the heat treatment, and the content of the ineffective secondary component nano-oxidation M in the target powder material is further reduced.
[0251] In addition, when the volume content of the matrix phase in the quick-setting alloy is low, the M element dissolved in the matrix phase is also low. Therefore, the content of the impurity minor component nano-oxidation M in the target powder material can also be reduced by reducing the volume content of the matrix phase in the quick-setting alloy. At this time, the b value is as high as possible, such as 8% ≤ b < 19.95%.
[0252] Fourth, when a nano-scale M-containing powder material has been obtained after the quick-setting alloy reacts with the acid, a wet sand milling process using non-ultrafine zirconium beads (the particle size of the zirconium beads is not less than 0.2 mm) is used to achieve: 1) dispersing the agglomerated M-containing powder particles in the slurry; 2) crushing the dendritic, tree-like, filamentous, and long rod-like particles in the slurry into short rod-like particles or nearly spherical particles; 3) obtaining a fresh surface of the M-containing powder material (removing the original passivation layer).
[0253] In the present application, the particle size of the M-containing powder material (nano Si / Ge powder formed by the dispersed particle phase in the rapid-setting alloy) is mainly related to the cooling rate of the rapid-setting alloy; the higher the cooling rate of the rapid-setting alloy, the smaller the particle size of the M-containing powder material. Therefore, the present application only needs to control the cooling rate of the rapid-setting alloy, and does not need to grind the Si / Ge powder to the nanometer level through multiple ball milling / sand milling by brute force according to the traditional wet ball milling; especially when it is necessary to grind to below 200nm, the traditional wet sand milling must use expensive ultrafine zirconia beads with a particle size of 0.1mm. After obtaining the M-containing powder material, the present application only needs to use coarser zirconia beads to disperse the powder. At the same time, the dendritic, branch-like, filamentous, and long rod-like particles in the dispersed particle phase are also very easy to be broken into short rod-like particles or nearly spherical particles by coarser dispersing zirconia beads.
[0254] Fifth, the selection of slurry solvent for wet ball milling / sand milling is determined, that is, the solvent in the slurry is mainly a non-aqueous solvent, so that through the optimization of the solvent, the degree of powder oxidation is reduced, the decomposition of hydrogen by water is reduced, and the cost of the sand milling process is reduced.
[0255] Therefore, the method described in the present application can use low-purity raw materials, and through the innovation of smelting equipment and quick-setting means, a quick-setting alloy with fine dispersed particle phase can be obtained on a large scale and at low cost. By heat treating the quick-setting alloy, the yield of the dispersed particle phase is further improved, and the content of the invalid composition of the oxide M is reduced. In the process of ball milling or sand milling, the preparation of ultrafine nano-Si / Ge powder materials with good dispersibility is achieved by using non-aqueous solvents and coarser grinding beads. The prepared nano-Si / Ge powder materials have good application prospects in catalytic materials, powder metallurgy, composite materials, coatings, battery negative electrode materials, and silicon-carbon negative electrodes. DETAILED DESCRIPTION
[0256] Hereinafter, the preparation method of the powder material will be further described through the following specific examples.
[0257] Example 1
[0258] This embodiment provides a method for preparing a nano-Si powder material, comprising the following steps:
[0259] Using Al ingots with a total atomic content of about 0.5% of Fe, Cu, and Mn, and Si ingots with a total atomic content of about 0.5% of Fe and Ca as the main raw materials, induction melting under atmospheric conditions yielded a molten Si alloy with an average composition of about Al. 84.5 Si 15 T 0.5 An initial alloy melt (T-type elements include Fe, Cu, Mn, Ca) is prepared, and the initial alloy melt is rapidly solidified into a rapid-solidified alloy strip with a thickness of ∼30 μm by a copper roller strip throwing method.
[0260] The solidification structure of the quick-solidified alloy strip is mainly composed of Al 97.4 Si 1.6 T 0.6 The matrix phase has a large atomic percentage composition of about Al 0.05 Si 99.85 T 0.1 The dispersed particle phase is composed of Al solid solution in the dispersed particle phase and Si solid solution in the matrix phase; the particle size range of the dispersed particle phase is 3nm to 150nm.
[0261] The quick-setting alloy strip is reacted with a hydrochloric acid solution. By utilizing the characteristics that the Al-rich matrix phase in the quick-setting alloy is easy to react and dissolve with the acid solution, while the Si-rich dispersed particle phase is not easy to react with the acid solution, the Si-rich dispersed particle phase is freely separated from the quick-setting alloy, and a solid-liquid mixture consisting of a nano-Si powder material mainly composed of the original dispersed particles and a corresponding reaction solution is obtained; at the same time, the Si dissolved in the matrix phase is mainly converted into nano-silicon dioxide.
[0262] The solid-liquid mixture is first pre-separated by a static sedimentation method to obtain a slurry mixture containing nano-Si powder material, and then the solution in the slurry is thrown out through the filter holes of the centrifuge filter cloth by centrifugation to obtain a slurry mixture with as high a solid content as possible, and then the mixture is repeatedly washed with water 4 times and centrifuged 4 times to obtain an undispersed nano-Si powder slurry with as little AlCl3 residue as possible. The main component of the undispersed nano-Si powder material is nano-Si with roughly passivated particle surfaces, and the volume percentage of dendrite-shaped, tree-shaped, filamentous, and long rod-shaped (aspect ratio greater than 3) particles in all nano-Si particles exceeds 20%;
[0263] The undispersed nano-Si powder slurry was dried to remove moisture, and then the dried undispersed nano-Si powder was mixed with anhydrous ethanol at a volume ratio of 1:9 to obtain a slurry, which was then dispersed in a sand mill for 1 hour, wherein the particle size of the zirconia beads in the sand mill was 0.3 mm.
[0264] The sand-milled slurry is dried under a nitrogen atmosphere, and the ethanol in the slurry is recovered to obtain a nano-Si powder material with good dispersibility.
[0265] The main component of the nano-Si powder material is nano-Si, and its average composition is mainly Al 0.05 Si 99.85 T 0.1 The Al solid solution exists in the average composition of Al 0.05 Si 99.85 T 0.1 of nano-Si; the secondary components of the nano-Si powder material include a small amount of residual AlCl3 salt and nano-silicon dioxide; wherein the molar percentage content of AlCl3 salt is about 0.2%; the molar percentage content of nano-silicon dioxide (nano-Si oxide) is about 10%; the particle size of the nano-silicon dioxide is less than 25nm; the particle size range of the nano-Si particles is 3nm to 150nm; the particle shape of the nano-Si is mainly at least one of spherical, nearly spherical, and short rod-shaped, and the volume percentage of the nano-Si particles, dendritic, tree-like, filamentous, and long rod-shaped (aspect ratio greater than 3) powder particles is less than 15%.
[0266] Example 2
[0267] This embodiment provides a method for preparing a nano-Si powder material, comprising the following steps:
[0268] A Zn ingot with a total atomic content of about 0.05% of Fe and Cu and a low-purity Si ingot with a total atomic content of about 1% of Fe and Ca were used as raw materials. The two were added into a high-strength and high-pressure closed container in a molar ratio of 6:1, and then heated to a completely mutually molten state at 1150°C to obtain a Zn ingot with an average composition of about 85.8 Si 14 T 0.2 The space outside the melt in the high-strength and high-pressure resistant closed container is less than 1%, thus effectively solving the problem of melt oxidation and Zn volatilization in the melt (if the space outside the melt in the container is large, the melt is easy to oxidize and Zn is also easy to volatilize).
[0269] The jet holes at the bottom of the high-strength and high-pressure resistant closed container are opened (the number of jet holes is 100, and the aperture is 20μm), and pressure is applied to the alloy melt in the high-strength and high-pressure resistant closed container at the same time, so that the pressure at the jet holes reaches more than 10Mpa, and the alloy melt in the high-strength and high-pressure resistant closed container is ejected from the jet holes under the action of pressure, and then immediately injected into high-speed flowing water, and irregular-shaped wire-like quick-solidifying alloys with a diameter of 20μm-40μm are obtained through water quenching.
[0270] The solidification structure of the wire-shaped rapid solidification alloy is mainly composed of Zn 99.67 Si 0.1 T 0.23 The matrix phase with a large atomic percentage composition of about Zn 0.05 Si 99.85 T 0.1 The dispersed particle phase is composed of Zn solid solution in the dispersed particle phase and a small amount of Si solid solution in the matrix phase. The particle size of the dispersed particle phase ranges from 3nm to 200nm.
[0271] The filamentary quick-setting alloy is reacted with a hydrochloric acid solution, and the Si-rich dispersed particle phase is freely separated from the quick-setting alloy by utilizing the characteristics that the Zn-rich matrix phase in the quick-setting alloy is easy to react and dissolve with the acid solution, while the Si-rich dispersed particle phase is not easy to react with the acid solution, so as to obtain a solid-liquid mixture consisting of a nano-Si powder material mainly composed of the original dispersed particles and a corresponding reaction solution; the extremely small amount of Si dissolved in the matrix phase is mainly converted into silicon dioxide.
[0272] The solid-liquid mixture is first pre-separated by static sedimentation to obtain a slurry mixture containing nano-Si powder material, and then the solution in the slurry is thrown out through the filter holes of the centrifuge filter cloth by centrifugation to obtain a slurry mixture with as high a solid content as possible, and then the mixture is repeatedly washed with water 4 times and centrifuged 4 times to obtain an undispersed nano-Si powder slurry with as little ZnCl2 residue as possible. The main component of the undispersed nano-Si powder material is nano-Si with passivated particle surface, and the volume percentage of dendrite-shaped, branch-shaped, filament-shaped, and long rod-shaped (aspect ratio greater than 3) particles in all nano-Si particles exceeds 20%;
[0273] The undispersed nano-Si powder slurry was dried to remove moisture, and then the dried undispersed nano-Si powder was mixed with anhydrous ethanol at a volume ratio of 1:6 to obtain a slurry, which was then processed in a sand mill for 1 hour, wherein the particle size of the zirconia beads in the sand mill was 0.3 mm.
[0274] The sand-milled slurry is dried under a nitrogen atmosphere, and the ethanol in the slurry is recovered to obtain a nano-Si powder material with good dispersibility.
[0275] The main component of the nano-Si powder material is nano-Si, and its average composition is mainly Zn 0.05 Si 99.85 T 0.1 The Zn solid solution exists in the average composition mainly Zn 0.05 Si 99.85 T 0.1 of nano-Si; the secondary components of the nano-Si powder material include a small amount of residual ZnCl2 salt and nano-silicon dioxide; wherein the molar percentage content of the ZnCl2 salt is about 0.1%; the molar percentage content of the nano-silicon dioxide (nano-Si oxide) is about 1%; the particle size of the nano-silicon dioxide is less than 25nm; the particle size range of the nano-Si particles is 3nm to 150nm; the particle shape of the nano-Si is mainly at least one of spherical, nearly spherical, and short rod-shaped, and the volume percentage of the powder particles of dendrites, branches, filaments, and long rods (aspect ratio greater than 3) in the nano-Si particles is less than 10%.
[0276] Example 3
[0277] This embodiment provides a method for preparing a nano-Si powder material, comprising the following steps:
[0278] Using Al ingots with a total atomic content of about 0.5% of Fe, Cu, and Mn, and Si ingots with a total atomic content of about 0.5% of Fe and Ca as raw materials, induction melting in an atmospheric environment yielded a product with an average composition of about Al84.5 Si 15 T 0.5 An initial alloy melt (T-type elements include Fe, Cu, Mn, Ca) is prepared, and the initial alloy melt is rapidly solidified into a rapid-solidified alloy strip with a thickness of ∼30 μm by a copper roller strip throwing method.
[0279] The solidification structure of the quick-solidified alloy strip is mainly composed of Al 97.4 Si 1.6 T 0.6 The matrix phase and the bulk atomic percentage composition are Al 0.05 Si 99.85 T 0.1 The dispersed particle phase is composed of Al, Si, and the dispersed particle phase is solid-dissolved in the dispersed particle phase, and the dispersed particle phase has a particle size ranging from 3 nm to 200 nm.
[0280] The quick-solidifying alloy strip is heat-treated at 300° C. for 72 hours to obtain a quick-solidifying alloy strip after heat treatment, and its solidification structure mainly consists of Al 98.87 Si 0.5 T 0.62 The matrix phase has a large atomic percentage composition of about Al 0.04 Si 99.88 T 0.08 The Si content in the matrix phase is significantly reduced and exists as a newly precipitated dispersed particle phase.
[0281] The rapid-setting alloy strip is reacted with a hydrochloric acid solution, and the Si-rich dispersed particle phase is freely separated from the rapid-setting alloy by utilizing the characteristics that the Al-rich matrix phase in the rapid-setting alloy is easy to react and dissolve with the acid solution, while the Si-rich dispersed particle phase is not easy to react with the acid solution, so as to obtain a solid-liquid mixture consisting of a nano-Si powder material mainly composed of the original dispersed particles and a corresponding reaction solution; the solid-solution Si precipitated in the matrix phase that is not completely heat-treated is mainly converted into silicon dioxide.
[0282] The solid-liquid mixture is first pre-separated by static sedimentation to obtain a slurry mixture containing nano-Si powder material, and then the solution in the slurry is thrown out through the filter holes of the centrifuge filter cloth by centrifugation to obtain a slurry mixture with as high a solid content as possible, and then the mixture is repeatedly washed with water 4 times and centrifuged 4 times to obtain an undispersed nano-Si powder slurry with as little AlCl3 residue as possible. The main component of the undispersed nano-Si powder material is nano-Si with passivated particle surface, and the volume percentage of dendrite-shaped, tree-shaped, filamentous, and long rod-shaped (aspect ratio greater than 3) particles in all nano-Si particles exceeds 20%;
[0283] The undispersed nano-Si powder slurry was dried to remove moisture, and then the dried undispersed nano-Si powder was mixed with anhydrous ethanol at a volume ratio of 1:6 to obtain a slurry, which was then processed in a sand mill for 1 hour, wherein the particle size of the zirconia beads in the sand mill was 0.3 mm.
[0284] The sand-milled slurry is dried under a nitrogen atmosphere, and the ethanol in the slurry is recovered to obtain a nano-Si powder material with good dispersibility.
[0285] The main component of the nano-Si powder material is nano-Si, and its average composition is mainly Al 0.04 Si 99.88 T 0.08 ; The secondary components of the nano-Si powder material include a small amount of residual AlCl3 salt and nano-silicon dioxide; wherein the molar percentage content of AlCl3 salt is about 0.15%; the molar percentage content of nano-silicon dioxide (Si oxide) is about 3.5%; the particle size of the nano-silicon dioxide is less than 25nm; the particle size range of the nano-Si particles is 3nm to 150nm; the particle shape of the nano-Si is mainly at least one of spherical, nearly spherical, and short rod-shaped, and the volume percentage of the nano-Si particles in the form of dendrites, branches, filaments, and long rods (aspect ratio greater than 3) is less than 15%.
[0286] Example 4
[0287] This embodiment provides a method for preparing a nano-Ge powder material, comprising the following steps:
[0288] Using a Zn ingot with a total atomic content of about 0.05% of Fe and Cu and a low-purity Ge ingot with a total atomic content of about 1% of Fe and Ca as raw materials, the two were heated to 500°C in an electric resistance furnace in an atmospheric environment and smelted to obtain a Zn ingot with an average composition of about 9:1. 89.85 Ge 10 T 0.15 The initial alloy melt (T-type elements include Fe, Cu, Mn, Ca. Since the Zn-Ge alloy has a low melting temperature and does not volatilize seriously, atmospheric melting can be used) is rapidly solidified into a rapid-solidification alloy strip with a thickness of 20 to 35 μm by a copper roller spinning method. The solidification structure of the rapid-solidification alloy strip is mainly composed of Zn with an atomic percentage of about 99.63 Ge 0.2 T 0.17 The matrix phase has a large atomic percentage composition of about Zn 0.1 Ge 99.85 T 0.05 The dispersed particle phase has a particle size range of 3nm to 200nm.
[0289] The rapid-setting alloy strip is reacted with a hydrochloric acid solution, and the characteristic that the Zn-rich matrix phase in the rapid-setting alloy is easy to react and dissolve with the acid solution, while the Ge-rich dispersed particle phase is not easy to react with the acid solution, is utilized to achieve the free separation of the Ge-rich dispersed particle phase from the rapid-setting alloy, and obtain a solid-liquid mixture consisting of a nano-Ge powder material mainly composed of the original dispersed particles and a corresponding reaction solution; the Ge dissolved in the matrix phase is mainly converted into germanium dioxide.
[0290] The solid-liquid mixture is first pre-separated by static sedimentation to obtain a slurry mixture containing nano-Ge powder material, and then the solution in the slurry is thrown out through the filter holes of the centrifuge filter cloth by centrifugation to obtain a slurry mixture with as high a solid content as possible, and then the mixture is repeatedly washed with water 4 times and centrifuged 4 times to obtain an undispersed nano-Ge powder slurry with as little ZnCl2 residue as possible. The main component of the undispersed nano-Ge powder material is nano-Ge with passivated particle surface, and the volume percentage of dendrite-shaped, branch-shaped, filament-shaped, and long rod-shaped (aspect ratio greater than 3) particles in all nano-Ge particles exceeds 20%;
[0291] The undispersed nano-Ge powder slurry was dried to remove moisture, and then the dried undispersed nano-Ge powder was mixed with anhydrous ethanol at a volume ratio of 1:7 to obtain a slurry, which was then processed in a sand mill for 2 hours, wherein the particle size of the zirconia beads in the sand mill was 0.5 mm.
[0292] The sand-milled slurry is dried under an argon protective atmosphere, and the ethanol in the slurry is recovered to obtain a nano-Ge powder material with good dispersibility.
[0293] The main component of the nano-Ge powder material is nano-Ge, and its average composition is mainly Zn 0.1 Ge 99 . 85 T 0.05 The secondary components of the nano-Ge powder material include a small amount of ZnCl2 salt residual from cleaning and nano-germanium dioxide; wherein the molar percentage content of the ZnCl2 salt is about 0.5%; the molar percentage content of nano-germanium dioxide (nano-Ge oxide) is about 2% (its source includes oxidation of Ge in the original matrix phase, and also includes the peeling of germanium dioxide on the surface of particles during sand grinding); the particle size of the nano-germanium dioxide is less than 25nm; the particle size range of the nano-Ge particles is 3nm to 200nm; the particle shape of the nano-Ge is mainly at least one of spherical, nearly spherical, and short rods, and in the nano-Ge particles, the volume percentage content of dendritic, tree-like, filamentous, and long rod-like (aspect ratio greater than 3) powder particles is less than 15%.
[0294] Example 5
[0295] This embodiment provides a method for preparing a nano-SiGe powder material, comprising the following steps:
[0296] Using Zn ingots with a total atomic content of about 0.5% of Fe and Cu, Al ingots with a total atomic content of about 0.5% of Fe, Cu and Mn, Si ingots with a total atomic content of about 0.5% of Fe and Ca, and low-purity Ge ingots with a total atomic content of about 0.5% of Fe and Ca as the main raw materials, induction melting under atmospheric environment resulted in an average composition of about Al 70 Zn 13.5 Si8Ge8T 0.5 The initial alloy melt (T-type elements include Fe, Cu, Mn, Ca) is atomized into a quick-setting alloy powder with a particle size of 5μm-150μm by water atomization powder making technology.
[0297] The solidification structure of the quick-setting alloy powder is mainly composed of Al 81.9 Zn 15.8 Si 1.5 Ge 0.2 T 0.6 The matrix phase with a large atomic percentage composition of about Al 0.05 Zn 0.05 Si 49 .1Ge 50.7 T 0.1 The dispersed particle phase is composed of a dispersed particle phase, and the particle size range of the dispersed particle phase is 20nm to 500nm.
[0298] The quick-setting alloy powder is reacted with a hydrochloric acid solution, and the Si / Ge-rich dispersed particle phase is freely separated from the quick-setting alloy by utilizing the characteristics that the Al / Zn-rich matrix phase in the quick-setting alloy is easy to react and dissolve with the acid solution, while the Si / Ge-rich dispersed particle phase is not easy to react with the acid solution, so as to obtain a solid-liquid mixture composed of a nano-Si / Ge powder material mainly composed of the original dispersed particles and a corresponding reaction solution; the Si / Ge dissolved in the matrix phase is mainly converted into nano-silicon dioxide / germanium.
[0299] The solid-liquid mixture is first pre-separated by static sedimentation to obtain a slurry-like mixture containing nano-Si / Ge powder material, and then the solution in the slurry is thrown out through the filter holes of the centrifuge filter cloth by centrifugation to obtain a slurry-like mixture with as high a solid content as possible, and then the mixture is repeatedly washed with water 4 times and centrifuged 4 times to obtain a nano-Si / Ge powder slurry with as little undispersed AlCl3 and ZnCl2 as possible. A small amount of hydrofluoric acid is added during the third water washing to reduce the content of nano-silicon dioxide / germanium. The main component of the undispersed nano-Si / Ge powder material is nano-Si / Ge with passivated particle surface, and the volume percentage of dendritic, branch-like, filamentous, and long rod-like (aspect ratio greater than 3) particles in the nano-Si / Ge particles exceeds 20% in all nano-Si / Ge particles;
[0300] The undispersed nano-Si / Ge powder slurry was dried to remove moisture, and then the dried undispersed nano-Si / Ge powder was mixed with anhydrous ethanol at a volume ratio of 1:8 to obtain a slurry, which was then dispersed in a sand mill for 1 hour, wherein the particle size of the zirconia beads in the sand mill was 0.4 mm.
[0301] The sand-milled slurry is dried under a nitrogen atmosphere, and the ethanol in the slurry is recovered to obtain a nano-Si / Ge powder material with good dispersibility.
[0302] The main components of the nano-Si / Ge powder material are nano-Si / Ge, and the average composition thereof is mainly Al 0.05 Zn 0.05 Si 49.1 Ge 50.7 T 0.1 ; The secondary components of the nano Si / Ge powder material include a small amount of AlCl3 salt and ZnCl2 salt residual from cleaning, and a small amount of nano germanium dioxide / silicon; wherein the molar percentage content of AlCl3 salt and ZnCl2 salt is about 0.5%; the molar percentage content of nano germanium dioxide / silicon is about 2% (after being treated with hydrofluoric acid, its content is greatly reduced); the particle size of the nano germanium dioxide / silicon is less than 15nm; the particle size range of the nano Si / Ge particles is 20nm to 500nm; the particle shape of the nano Si / Ge is mainly at least one of spherical, nearly spherical, and short rod-shaped, and the volume percentage of the nano Si / Ge particles of dendritic, tree-like, filamentous, and long rod-shaped (aspect ratio greater than 3) powder particles is less than 15%.
[0303] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0304] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A method for preparing nano Si / Ge powder material, characterized in that: The following steps are involved: Step 1: Select an initial alloy raw material containing T elements, melt the initial alloy raw material, and obtain a uniform initial alloy melt containing T elements, wherein the T elements include at least one of Fe, Cu, Mn, Mg, Ca, and Cd; the average composition of the initial alloy melt is A a M b T d , and M includes at least one of Si and Ge, and A includes at least one of Zn, Sn, Pb, Ga, In, Ag, Bi, and Al; wherein a, b, and d represent the atomic percentage content of the corresponding constituent elements, and 70%<a<99.39%, 0.6%<b<29.99%, and 0.01%<d≤9.5%; Step 2: The initial alloy melt is prepared into a quick-setting alloy by a rapid solidification technology, wherein the solidified structure of the quick-setting alloy includes a matrix phase and a dispersed particle phase; the melting point of the matrix phase is lower than the melting point of the dispersed particle phase, and the dispersed particle phase is coated in the matrix phase; during the solidification process of the initial alloy melt, the T-type elements in the initial alloy melt are redistributed in the dispersed particle phase and the matrix phase, and are enriched in the matrix phase, thereby depleting the T-type elements in the dispersed particle phase; in the quick-setting alloy, the average composition of the dispersed particle phase is mainly A x1 M y1 T z1 , and the A element therein exists as a solid solution in the dispersed particle phase; the average composition of the matrix phase is mainly A x2 M y2 T z2 , and the M element exists in the matrix phase as a solid solution; wherein 0<x1≤1%, 98.0%≤y1<100%, 0<z1<1.5%; 81%≤x2<99.95%, 0.05%<y2<2.5%, 0<z2<18.95%, z1<d<z2; x1, y1, z1, x2, y2, z2 represent the atomic percentage content of the corresponding constituent elements respectively; Step 3, reacting the quick-setting alloy with an acid solution, utilizing the characteristics that the matrix phase in the quick-setting alloy is easy to react and dissolve with the acid solution, while the dispersed particle phase is not easy to react with the acid solution, to achieve the free separation of the dispersed particle phase from the quick-setting alloy, and obtain a solid-liquid mixture consisting of a nano-M powder material mainly composed of the original dispersed particles and the corresponding reaction solution; Step 4, separating the solid-liquid mixture obtained above, and repeatedly washing the obtained solid product to obtain an undispersed nano-Si / Ge powder material; the main component of the undispersed nano-Si / Ge powder material is nano-M with passivated particle surface, and the volume percentage of dendritic, branch-like, filamentous, and long rod-like (aspect ratio greater than 3) particles in all nano-M particles exceeds 20%; at the same time, the secondary components of the undispersed nano-Si / Ge powder material also include a small amount of A salt and nano-oxide M; wherein the molar percentage content of A salt is greater than 0 and less than 3%; the molar percentage content of nano-oxide M is greater than 0 and less than 25%; Step 5, mixing the above-obtained undispersed nano-Si / Ge powder material with a solvent mainly composed of non-aqueous materials to form a slurry, and then ball milling or sand milling for a period of time in a ball mill or sand mill; Step 6: The slurry obtained above is subjected to solid-liquid separation, and the solid powder material is collected to obtain a nano-Si / Ge powder material with good dispersibility; the nano-Si / Ge powder material is composed of a main component and a secondary component; the main component of the nano-Si / Ge powder material is nano-M, and its average component is mainly A x1 M y1 T z1 or A x3 M y3 T z3 , wherein 0<x1≤1%, 98.5%≤y1<100%, 0<z1<1.5%; 0<x3≤0.5%, 99%≤y3<100%, 0<z3<1%; x1, y1, z1, x3, y3, z3 represent the atomic percentage content of the corresponding constituent elements respectively; the A solid solution exists in the average composition mainly A x1 M y1 T z1 or A x3 M y3 T z3 The secondary components of the nano Si / Ge powder material include a small amount of A salt and nano M oxide; wherein the molar percentage content of the A salt is greater than 0 and less than 3%; the molar percentage content of the nano M oxide is greater than 0 and less than 25%; the particle size of the nano M oxide is less than 25nm; the particle size range of the nano M particles is 3nm to 500nm; the particle shape of the nano M is mainly at least one of spherical, nearly spherical, and short rods, and among the nano M particles, the volume percentage content of dendritic, branch-like, filamentous, and long rod-like (aspect ratio greater than 3) powder particles is less than 20%.
2. The method for preparing nano Si / Ge powder material according to claim 1, characterized in that: The initial alloy is melted in a positive pressure closed container.
3. The method for preparing nano Si / Ge powder material according to claim 1, characterized in that: The rapid solidification technology includes at least one of melt stripping and melt jet water quenching.
4. The method for preparing nano Si / Ge powder material according to claim 1, characterized in that: The initial alloy melting condition is positive pressure closed container melting, the rapid solidification technology includes melt jet water quenching, and the average aperture of the jet hole is 1μm-2mm; the number of jet holes corresponding to the positive pressure closed container exceeds 2.
5. The method for preparing nano Si / Ge powder material according to claim 1, characterized in that: The particle size of the dispersed particle phase ranges from 3nm to 500nm.
6. The method for preparing nano Si / Ge powder material according to claim 1, characterized in that: After step 2 and before step 3, a heat treatment process for the quick-setting alloy is added, and the heat treatment temperature of the quick-setting alloy is 150°C. - 550℃.
7. The method for preparing nano Si / Ge powder material according to claim 6, characterized in that: The average composition of the dispersed particle phase after heat treatment is mainly A x3 M y3 T z3 ; The average composition of the matrix phase after heat treatment is mainly A x4 M y4 T z4 ; Among them, 0<x3≤0.5%, 99%≤y3<100%, 0<z3<1%; 81%≤x4<99.98%, 0.02%<y4<1.5%, 0<z4<18.98%; Among them, x3, y3, z3, x4, y4, z4 respectively represent the atomic percentage content of the corresponding constituent elements; and y4<y2.
8. The method for preparing nano Si / Ge powder material according to claim 1, characterized in that: The solid-liquid separation method in step 4 includes flotation solid-liquid separation.
9. The method for preparing nano Si / Ge powder material according to claim 1, characterized in that: During the repeated washing of the obtained solid product in step 4, an appropriate amount of hydrofluoric acid is added to the washing liquid in the early washing process.
10. The method for preparing nano Si / Ge powder material according to claim 1, characterized in that: The solvent mainly composed of non-aqueous solvent is mainly composed of organic solvent, and the content of organic solvent is more than 85%.
11. The method for preparing nano Si / Ge powder material according to claim 1, characterized in that: During the ball milling / sand milling process, the particle size of the grinding beads is 0.15 mm-5 mm.
12. The method for preparing nano Si / Ge powder material according to claim 1, characterized in that: The solid-liquid separation process in step six is carried out under a protective atmosphere.
13. The method for preparing nano Si / Ge powder material according to claim 1, characterized in that: M is mainly Si, A is mainly Zn, and the nano-Si / Ge powder material with good dispersibility obtained in step 6 is mainly a nano-Si powder material with good dispersibility, wherein the molar percentage content of nano-Si oxide is greater than 0 and less than 5%.
14. A nano-Si / Ge powder composite material, characterized in that: The powder composite material containing nano-Si / Ge is composed of a main component and a secondary component; the main component of the powder composite material containing nano-Si / Ge is nano-M, and its average composition is mainly A x1 M y1 T z1 or A x3 M y3 T z3 , wherein 0<x1≤1%, 98.5%≤y1<100%, 0<z1<1.5%; 0<x3≤0.5%, 99%≤y3<100%, 0<z3<1%; x1, y1, z1, x3, y3, z3 represent the atomic percentage content of the corresponding constituent elements respectively; the T-type element comprises at least one of Fe, Cu, Mn, Mg, Ca, Cd, M comprises at least one of Si and Ge, A comprises at least one of Zn, Sn, Pb, Ga, In, Ag, Bi, Al; the A solid solution exists in the average composition mainly A x1 M y1 T z1 or A x3 M y3 T z3 The secondary components of the nano-Si / Ge-containing powder composite material include a small amount of A salt and nano-oxidized M; wherein the molar percentage content of the A salt is greater than 0 and less than 3%; the molar percentage content of the nano-oxidized M is greater than 0 and less than 25%; the particle size of the nano-oxidized M is less than 25nm; the particle size range of the nano-M particles is 3nm to 500nm; the particle shape of the nano-M is mainly at least one of spherical, nearly spherical, and short rods, and among the nano-M particles, the volume percentage content of dendritic, branch-like, filamentous, and long rod-like (aspect ratio greater than 3) powder particles is less than 20%.
15. Use of the nano-Si / Ge powder material prepared by the method according to any one of claims 1 to 13 or the nano-Si / Ge-containing powder composite material according to claim 14 in catalytic materials, powder metallurgy, composite materials, coatings, battery negative electrode materials, and silicon-carbon negative electrodes.
16. A method for preparing a non-dispersed nano-Si / Ge powder material, characterized in that: Prepared by the method described in steps 1 to 4 of claim 1.